(untitled) (Jurnal Wahana Konseling, 2026)
This study aimed to examine the effectiveness of group guidance services using the positive reinforcement technique in improving reading interest among seventh-grade students at SMPN M Pekanbaru. A quantitative approach with a one-group pretest-posttest design was applied. The research was conducted from September 2025 to January 2026. The participants were 10 students selected through purposive sampling based on low and moderate reading interest categories. Data were collected using a reading interest scale consisting of 30 valid items with four Likert response options. The instrument demonstrated high reliability, with a Cronbach’s Alpha coefficient of 0.894. Data were analyzed using descriptive statistics, the Wilcoxon signed-rank test, and normalized N-Gain analysis. The findings showed that before the intervention, 70% of students were in the low category and 30% were in the moderate category. After eight treatment sessions, 60% of students moved to the moderate category and 40% reached the high category. The Wilcoxon test indicated a significant difference between pretest and posttest scores, with p = 0.005. The mean N-Gain score was 0.6784, indicating moderate effectiveness. These findings suggest that group guidance with positive reinforcement can improve students’ reading interest. This strategy may serve as a practical counseling intervention in junior high schools.